Effects of different types of non-cardiac surgical trauma on hippocampus-dependent memory and neuroinflammation - Lu, Bo; Yuan, Hui; Mo, Lan; Sun, Daofan; Liu, Rongjun; Zhou, Han; Zhai, Xiaojie; Wang, Ruichun; Chen, Junping; Meng, Bo (Frontiers in Behavioral Neuroscience, 2022)
Background Older individuals have been reported to suffer from cognitive disorders after surgery. Various types of surgical trauma have been used to set up postoperative cognitive dysfunction (POCD) animal models in preclinical studies. However, few comparative analyses of these animal models were conducted. Methods Tibial surgery, abdominal surgery, and extended abdominal surgery were performed on aged ICR mice to establish POCD models. Behavioral tests included open field, novel object recognition, fear conditioning, and Morris water maze. The Z-Score methodology was adopted to obtain a comprehensive and integrated memory performance profile. The changes in hippocampal neuroinflammation were analyzed by ELISA, PCR and immunofluorescence. Results In this study, we found that each type of non-cardiac surgical trauma has a different effect on locomotor activity. Tibial and extended abdominal surgeries led to more significant cognitive impairment than abdominal surgery did. Inflammatory cytokines peaked on postoperative day 1 and decreased to control levels on day 3 and day 7. Hippocampal neuroinflammation indicators among the three surgery types on postoperative day 1 had no statistical differences. Conclusion Overall, the type and intensity of non-cardiac surgical trauma can affect cognitive-behavioral outcomes and central inflammation. The shortcomings and emerging issues of POCD animal research methods need to be further studied and solved.